ANALISA UNJUK KERJA INDUCED DRAFT FAN PLTU ASAM-ASAM UNIT 3 DAN 4 - Syarief, Akhmad; Nugroho, Wisnu Setyo; Nugraha, Andy (INFO-TEKNIK, 2020)
Throughout the year 2015, PLTU Asam Asam Unit 3 and 4’s Induced draft fans frequently having issues. These issues were affects customer’s elecricity consumption because of load generated from PLTU Asam Asam unit 3 and 4 is was decreased heavily, seldom made the unit shut down for maintenance. This issues was being discussed and investigated to find the source and solutian to fix it. After the investigation, it is found that fly ash who was being carried by flue gas through IDF was stuck to fan’s blade and create unbalance in its rotation. Next modification was applied to fly ash transmitter to make sure its operating continous because it has been stopped for a while. The effect of this modification is quite significant if we compare data from before and after modification, it can be see that derating and shutdown because of IDF problem is fewer than what it was before modification.